Synthesis and Properties of a Flexible Curing Agent - Wang, X.; Zheng, S.R.; Wang, R.M. (Asian Journal of Chemistry, 2013)
This paper presents the synthesis of a new type of flexible epoxy curing agent and an approach to improve the toughness of epoxy resin by curing without reducing the strength and modulus of the resin-cured material. The results show that the degree of toughness reaches maximum values when the flexible curing agent is applied at weight percentages (wt. %) between 10 and 15 %. When the amount of flexible curing agent added to epoxy resin weight is 10 wt. %, the impact toughness and fracture toughness increases by 33.3 % and 96.3 %, respectively, compared with the pure epoxy resin. When the amount of flexible curing agent added to epoxy is 10 wt. %, the resulting impact thoughness of the material is 19.5 kJ m-2 at -50 ºC, the impact toughness of pure epoxy resin is only 7.96 kJ m-2.